Factors associated with staff retention in the NHS acute sector - Elaine Kelly; George Stoye; Max Warner (Institute for Fiscal Studies (IFS), 2022)
Against a backdrop of increasing demands for health care, the National Health Service (NHS) has long sought ways to increase the number of staff available to provide care to patients. More doctors, nurses, midwives and health-care assistants (HCAs) mean that the NHS can deliver more, and higher-quality, care. Increasing staff numbers is a clear policy priority, as reflected in the 2019 Conservative Party's manifesto commitment to increase the number of nurses by 50,000 by 2024, and demand for staff has only intensified in the wake of the pandemic and the subsequent backlog in elective care. In this report we add to this evidence base by examining how a range of individual staff characteristics, regional economic conditions and trust characteristics are associated with whether individual staff members decide to leave the NHS acute sector. We use the Electronic Staff Record (ESR), the monthly payroll of the NHS, to analyse how much of the variation in retention rates between NHS acute trusts can be explained by these characteristics, and to examine which factors were associated with the leaving decisions of medical consultants, nurses and midwives, and HCAs between 2012 and 2021.
Keywords: 330; Employment and income; Health and social care; Healthcare; Employment; Gender; Labour supply and workforce; NHS; Public sector